2022
DOI: 10.21203/rs.3.rs-1826165/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a health promoting university: descriptive findings on health, wellbeing and academic performance amongst university students in Australia

Abstract: Background: Universities are increasingly recognised as institutions where health and wellbeing can be promoted to maximise academic outcomes, career transitions, and lifelong positive health behaviours. There is concern about the mental health of university students and other factors which affect academic outcomes particularly for subgroups such as international students. There are few cohort studies of the breadth of issues that can impact on mental health and academic outcomes for both local and internation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Our findings converge with those of Sanci et al, 6 who found that the proportion of tertiary students reporting severe or moderately severe depression (as indicated by PHQ-9 cut-offs) was higher than among young people in the general population. There may be several reasons as to why tertiary students in this cohort experienced poorer mental health.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings converge with those of Sanci et al, 6 who found that the proportion of tertiary students reporting severe or moderately severe depression (as indicated by PHQ-9 cut-offs) was higher than among young people in the general population. There may be several reasons as to why tertiary students in this cohort experienced poorer mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Students experiencing high academic pressure are more likely to report depression and/or anxiety symptoms, while students with poor mental health are more likely to fail subjects, receive lower grades, and discontinue their studies. 6 Respondents to the 2016 Australian National Tertiary Student Wellbeing Survey 8 reported that anxiety, low mood, and feelings of hopelessness impacted their studies to the extent that they were unable to function on some days.…”
mentioning
confidence: 99%
See 3 more Smart Citations